Valve Heart Surgery in Brazil - The BYPASS Registry Analysis - Zilli,Alexandre Cabral (2020)
Abstract Objective: To analyze the profile and outcomes of patients who underwent valve heart surgery in Brazil, using information retrieved from the Brazilian Registry of Cardiovascular Surgeries in Adults (BYPASS Registry) database. Methods: This is a multicenter cohort study, evaluating 920 patients submitted to heart valve surgery. Demographics and postoperative clinical outcomes were assessed and compared to estimate mortality risk using the European System for Cardiac Operative Risk Evaluation (EuroSCORE). Results: Isolated aortic valve replacement was the most frequently performed surgery (34%), followed by isolated mitral valve replacement (24.9%). Valve repair was performed in 21% of mitral procedures. Minimally invasive access was performed in 1.6% and the most frequent postoperative complications were arrhythmias (22.6%), infections (5.7%), and low-output syndrome (5.1%). Operations covered by the public health system accounted for 80.8% and the hospital mortality rate was 7.3%. Conclusion: The most frequent isolated valve surgery in Brazil is the aortic valve replacement by conventional open access and the rheumatic disease is still the main etiology for valve surgery. The BYPASS Registry has a fundamental role to provide information on the profile of patients with valve heart disease in our country in order to delineate adequate strategies for health promotion and resource allocation for cardiac surgery.